Evaluating the Effectiveness of AI in Developing Digital Marketing Content for Certification Service Firms - Agus Sugiyato; Cicilia Sriliasta Bangun; Fikri Fauzi; Mulyati Mulyati; Omar Arif Al-Kamari (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
The implementation of Artificial Intelligence (AI) in digital marketing has become a major driver of business efficiency, yet its strategic implications and the role of human involvement still require in-depth study. This qualitative case study research aims to analyze the effectiveness of adopting generative AI (Gemini AI and Claude AI) in the content creation process at PT. Gaivo Solusi Manajemen, focusing on perceived usefulness, the role of human-in-the-loop, and the perspective of competitive advantage. Data were collected through semi-structured interviews with key informants and analyzed using Thematic Analysis. The findings indicate that AI substantially increases process efficiency, particularly in drafting content and SEO Meta packages, which boosts production volume and speed. However, key findings emphasize that AI is merely a supporting tool and necessitates mandatory supervision by expert staff (human-in-the-loop) to ensure information integrity and quality that complies with professional service industry regulations. Strategically, AI is not considered a source of hardly imitable competitive advantage (it is a commodity), but rather an enabler. The true competitive advantage lies in the staff’s ability in prompt engineering, supported by the company’s relevant internal data. This study provides managerial contributions by recommending a focus on investment in human resource skill development rather than solely on the acquisition of AI tools.